Factors Influencing Epiphytic Lichen Species Distribution in a Managed Mediterranean Pinus nigra Arnold Forest - ÇOBANOĞLU, GÜLŞAH (MDPI, 2019)
Lichens have important ecological functions in black pine forests, such as nitrogen fixation and nutrient cycling. Understanding lichen diversity could provide a better understanding of black pine ecosystems. The aim of this study was to identify the factors affecting the composition of lichen communities and their specific diversity in Mediterranean black pine forests. Research was conducted in 48 sampling plots. For the analysis, presence-absence and frequency data of lichen species were used. For stand level analysis, four community composition tables were created. We used bioclimate, topography, stand, and parent rock as variables. A total of 33 epiphytic lichen species were identified in the black pine forests from 282 sampled trees. Indicator lichen species were determined according to geographic region and stand age classes. Hypocenomyce scalaris was found to be an indicator species for old forests. Frequency data were more useful for revealing lichen species composition than presence-absence data. Of the topographic variables, elevation was the most prominent and had the highest explanation ratio for the composition of lichen species with a coefficient of correlation (R-2) value of 0.49. Significantly positive (p < 0.001) relationships were found between epiphytic lichen richness and tree crown height, tree height, and bark pH. Our results revealed that to retain the trees in the stands rich in lichen species diversity is recommended in the managed forests.
Keywords: lichen diversity; indicator species; species response curves; presence-absence data; frequency data; FUNCTIONAL DIVERSITY; CENTRAL PLATEAU; COMMUNITIES; BRYOPHYTES; RICHNESS; PATTERNS; TREE; INDICATOR; NORTHERN; DRIVERS